Off-label and unlicensed drug treatments in Neonatal Intensive Care Units: a systematic review - Fábio Reis; Rita Pissarra; Henrique Soares; Paulo Soares; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2021)
Newborns are particularly susceptible to off-label and unlicensed (OLUL) drug treatments, especially in the intensive care setting, inferring from dosing regimens and indications supported in older populations and built on non-neonatal pathophysiology. This use leads to unpredictable drug effectiveness and safety and, therefore, an increased probability of medication errors and adverse drug reactions. An extensive literature search was conducted in MEDLINE, Scopus, and Web of Science for papers published from 2011 to 2020 considering OLUL drug use in Neonatal Intensive Care Units (NICUs). Of the 902 studies retrieved, 618 after duplicates were removed, 74 full texts were carefully assessed for eligibility and, in the end, 23 published studies were included, representing a total of 6,762 patients in 80 NICUs worldwide. Considering overall prescriptions, 43.5% were OL and 11.1% were UL. Most studies found that more than 50% of the newborns were exposed to at least 1 OLUL drug and 10 of them reported a rate higher than 90%. Most prescribed drug classes in an OL manner were anti-infectives for systemic use drugs, including ampicillin and gentamicin, followed by nervous system drugs such as fentanyl. The most prescribed drug class in a UL manner was nervous system drugs, being caffeine the most prescribed one. The main reasons for OL prescribing included age and dose, and for UL prescribing, modifications of licensed drugs, extemporaneous preparations, or changes in the pharmaceutical forms. Very preterm, lower birth weight, disease severity, and longer length of stay in the NICU were associated with higher OLUL prescribing. These findings show that despite recent attempts by international regulatory authorities to develop more clinical trials in the pediatric population, OLUL drug use is still widespread, particularly among newborns in NICUs. More efforts must be made by these regulatory entities to ensure the development of safer drugs for the neonatal period.